The removal of remazol brilliant blue dyes from liquid waste using nano montmorillonite from bentonite of Bener Meriah Aceh - JULINAWATI JULINAWATI; FATHURRAHMI FATHURRAHMI; IRFAN MUSTAFA; DETA RAHMADANTI (Jurnal Natural, 2022)
Research on the potential of nano montmorillonite as an adsorbent for Remazol Brilliant Blue dye waste has been carried out. Nano montmorillonite was isolated from Bener Meriah bentonite, Aceh, to be used as an adsorbent. The optimum conditions for adsorption of Remazol Brilliant Blue dye using nano montmorillonite occurred at a contact time of 60 minutes, pH 4, and adsorbent mass of 2 grams. The results showed that the adsorption of Remazol Brilliant Blue dye by nano montmorillonite followed the Freundlich isotherm model with R2 = 0.9858. The results of the regeneration test show that the montmorillonite nano adsorbent can be used repeatedly